2008
DOI: 10.1590/s1807-59322008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Blind, Randomized, Controlled Trial of Pelvic Floor Muscle Training, Electrical Stimulation, Vaginal Cones, and No Active Treatment in the Management of Stress Urinary Incontinence

Abstract: PURPOSETo compare the effectiveness of pelvic floor exercises, electrical stimulation, vaginal cones, and no active treatment in women with urodynamic stress urinary incontinence.PATIENTS AND METHODSOne hundred eighteen subjects were randomly selected to recieve pelvic floor exercises (n=31), ES (n=30), vaginal cones (n=27), or no treatment (untreated control) (n=30). Women were evaluated before and after completion of six months of treatment by the pad test, quality of life questionnaire (I-QOL), urodynamic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
152
0
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 24 publications
6
152
0
21
Order By: Relevance
“…1 PFM training should be recommended as a first-line conservative management in the treatment of urinary incontinence, 2,3 as demonstrated by numerous randomized controlled trials. [4][5][6][7] The success of treatment with exercises is dependent on the achievement of strength and endurance, which consequently leads to improvement of the PFM function. Evaluation of PFM function is a difficult task, as there is no consensus regarding the best method to evaluate or control the effects of PFM training.…”
Section: Introductionmentioning
confidence: 99%
“…1 PFM training should be recommended as a first-line conservative management in the treatment of urinary incontinence, 2,3 as demonstrated by numerous randomized controlled trials. [4][5][6][7] The success of treatment with exercises is dependent on the achievement of strength and endurance, which consequently leads to improvement of the PFM function. Evaluation of PFM function is a difficult task, as there is no consensus regarding the best method to evaluate or control the effects of PFM training.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Castro et al 27 claim that these three different modes of therapy are equally effective for UUI and SUI. In the present study, the combination of exercise and electrical stimulation was shown to be effective as most of the participants reported being continent at the end of the treatment.…”
Section: Discussionmentioning
confidence: 92%
“…It is also essential that the professional caring for these women value not only the identification of factors related to reduced PFMS but also encourage them to practice exercises to strengthen the PF muscles and also to report complains related the genitourinary tract (6,9,(14)(15)17) . Performing perineometry is more important in the realization of pelvic floor exercises with biofeedback for treating these disorders (2)(3)5,(9)(10)(11)(12)(13)15) .…”
Section: Discussionmentioning
confidence: 99%
“…About one third of adult women have Urinary Incontinence (1)(2) (UI), which can impair a woman's physical, sexual, domestic, and professional and leisure activities (2)(3)(4) . Pregnancy, vaginal delivery, parity, duration of the second stage of labor, difficulty in fetal extraction during a cesarean section, newborn's weight, perineal trauma and other mechanical, endocrinal and neural factors can lead to reduction or loss of the pelvic floor muscle tone causing genitourinary disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) . Altered PFMS has been the focus of studies and research due to the evolution of equipment and exams that make its evaluation and prognosis more precise (10) .…”
Section: Introductionmentioning
confidence: 99%